Narratives of a conflict: discursive disputes about tourism in Barcelona (Intercom - Brazilian Journal of Communication Sciences, 2023)
The article aims to highlight the terms and narratives that supported the action of protagonists in the conflict over tourism in the city of Barcelona, Spain. A vast discursive load emerges from the clash between the agents involved in the conflict: businessmen from the tourism sector, City Hall, social movements, members of the Academy, producing their own lexicon, composed of terms such as overtourism, tourismphobia, anti-tourism, etc. In search of the meanings of such expressive and metaphorical communication, representatives of the involved segments were interviewed in loco, as the article intended to portray. The study showed an intense political and symbolic struggle among the agents, who use discursive resources in the search for legitimacy and power.
Keywords: Tourism; Barcelona; Conflict; Narratives; Speech